The visual report of the perak war based on selected newspaper Visuals from Britain and America, 1875-1876 - Azian Tahir; Arba’iyah Mohd Noor; Mohd Firdaus Abdullah; Syed Alwi Syed Abu Bakar (Penerbit Universiti Kebangsaan Malaysia, 2023)
This study aims to investigate the representation of ideas through the visuals of The Perak War in Malaya, as produced by selected illustrated newspapers from Britain and America such as The Graphic, The Illustrated London News, and Frank Leslie's Illustrated Newspaper from 1875 to 1876. Discussing the content and the objective behind the visual publication of The Perak War, which involved the hunt of J.W.W. Birch murderers and the Malay resistance against the British colonial authority in Pasir Salak, Perak, is the major objective of this research. In fact, the theme of this study is history, which is conducted by applying the qualitative method. Based on previous studies, research which was centred on the Perak War visuals did not get a lot of attention from researchers even though it was able to offer new interpretations of historical events involving Malaya. Most articles written on the Perak War were derived from written sources such as British records, individual records, letters, books, oral input, and others. Consequently, the dynamics of national history are lacking due to the limitations caused by these resources. Findings indicate that the objective in producing the Perak War visuals by the resources mentioned differs from the publication goal. Nevertheless, overall, there are similarities in the objective behind visual productions listed in this study which was to represent the British’s interest in Malaya and also to consolidate the imperial image of its colonies.